Indonesian Land Resources: Potency, Problems, and Utilization Strategy - HIDAYAT, ACHMAD (Indonesian Center for Agriculture Land Resource Development, 2009)
Indonesia mainland has variety of soils, parent materials, landforms, elevations and climates. This condition is the main capitals to produce sustainable agricultural commodities. The utilization of land resources to develop agriculture should consider its potentials in gaining the optimum results. Up to now the agricultural area used for agricultural purposes cover 70.2 million hectares consisting of rice field, upland crop field, yard, plantation, grazing land, trees, and fish pond. Based on the assessment results by Indonesian Agency for Agricultural Research and Development, the land in Indonesia which is potential or suitable for agriculture covers 94 million hectares, comprising 25.4 million hectares of wetland (rice field) and 68.6 million hectares of upland/ dryland. There are 30.67 million hectares of the total area which is potential for agricultural extensification comprising of 8.28 million hectares annual wetland agriculture (rice field), 7.08 million hectares annual upland agriculture, and 15.31 million hectares perennial agriculture. Wetland for annual crops covers swampy land with the total of 2.98 million hectares (mainly in Papua) and non swampy land 5.30 million hectares. In Indonesia the potential land as well as available land for agricultural extensification is still sufficient, but by the increasing needs of land for agriculture and non-agriculture, careful utilization is needed. The landuse competition in the future as a consequences to keep national food security and develop bioenergy needs to be overcome. Some efforts that can be done are by increasing the productivity (intensification), correct landuse based extensification, and developing primary technological innovation.